PERSONA AND SHADOW IN SHATTERDAY BY HARLAN ELLISON AND FIGHT CLUB BY CHUCK PALAHNIUK - Na'ilah Dian Ekaputri; Abu Fanani (STKIP PGRI Jombang, 2022)
This study aims at analyzing The Persona and The Shadow in two literary works, Shatterday a by Harlan Ellison and Fight Club by Chuck Palahniuk which show the mental disorders of the main characters. Sometimes, some people are confused with what happen in their life and it makes them create a “new” personality to “explain” and express what they feel. In these literary works, the main characters “use” other personality to express their feeling and make them realized with the reality.This study is conducted to enrich the topic about persona and shadow. The writeruses qualitative approach in relation to the use of clear and systematic description about the phenomena being studied and used psychoanalysis as the main theory of Carl G. Jung. The data are collected from two literary works, Shatterday and Fight Club .This study reveals that the persona and the shadow in the stories are almost different. The persona is the same person that is confused with their life. Novins, in Shatterday, is a man who lives alone in his apartment and always run from his true life. Novins would not face anything with a realistic mind and he prefers to create someone that he thinks he is an ideal man. That is Jay. Meanwhile in Fight Club, the narrator creates someone who can give him a satisfaction and can be a savior to help him escape from his boring life. That is Tyler Durden. The arrangement of these two stories is almost same. Novins tries to make a peace with the shadow and he surrendered with his shadow, in a good way, means that Novins willing to give his body and his life to Jay, in order to became a better person. Whereas the narrator try to make a peace with his shadow because of he thinks that what the shadow has done is wrong.